Renegotiation in Finitely Repeated Games - Benoit, Jean-Pierre; Krishna, Vijay (Econometrica, 1993)
Perfect equilibria of finitely repeated games may be vulnerable to the possibility of renegotiation among players. We study the limiting properties of the set of payoffs from equilibria that are immune to renegotiation. Our main result is that the limit of the set of payoffs from renegotiation proof equilibria is either a singleton or a connected subset of the Pareto efficient frontier. A simple sufficient condition for the latter to occur is also provided.